Adequate application of chicken manure could relieve the damage caused by Cd to E. breviscapus plants - Jia, Lijie; Wen, Shuhan; Zhang, Jingling; Wang, Peili; Chen, Yu; Zhao, Ping; Fan, Wei; Zhou, Yanli; Yang, Shengchao; Long, Guangqiang (Frontiers in Plant Science, 2025)
IntroductionCadmium (Cd) pollution leads to the decrease of the yield and active ingredient content of medicinal plants, and the accumulation of Cd in these plants present potential safety risks for medicinal applications. Exploring effective measures for the safe cultivation of medicinal plants, particularly those with strong capacity for Cd accumulation, is crucial to ensure the safety and quality of medicinal materials.MethodsIn this study, E. breviscapus, a medicinal plant with a relatively greater capacity for Cd accumulation, was selected for a pot experiment. The experiment was conducted using soil artificially contaminated with 100 mg kg−1 of Cd to evaluate the effects of different application rates of chicken manure (0, 10, 30, and 60 g kg−1, designated as CM0, CM10, CM30, and CM60, respectively). The optimal application amount of chicken manure (CM) was determined, and the underlying mechanisms of CM improving the yield and active ingredient contents of E. breviscapus was explored from the physiological response of plants and the forms and content of Cd in soil.ResultsThe results showed that compared with the CM0, the soil Cd content decreased by 7.0% under CM30 and by 12.3% under CM60. The plant yield increased by 32% in the CM60, while scutellarin content increased by 2.28, 1.92, and 2.72-fold in CM10, CM30, and CM60, respectively. Among all treatments, CM60 demonstrated the most pronounced effect in reducing shoot Cd levels and enhancing both plant yield and scutellarin content. Structural equation modeling (SEM) analysis revealed that the increase of plant yield was primarily attributed to Pn, whereas the enhancement in scutellarin content was associated with shoot Cd concentration and CAT activity in plants.ConclusionsIn summary, this study demonstrates a feasible and environmentally sustainable approach to the safe cultivation of medicinal plants, with the dual benefits of maintaining yield and enhancing active ingredients content.